2019
DOI: 10.4103/ijpvm.ijpvm_46_18
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate interventions for pregnant women with indicators of metabolic syndrome on pregnancy outcomes: A systematic review

Abstract: Metabolic syndrome (MetS), a series of symptoms, including abdominal obesity, impaired glucose tolerance and insulin metabolism, hypertension, and dyslipidemia, is considered as the risk of developing cardiovascular disease and diabetes that can predispose a pregnant women to serious health problem, women in the developed as well as the developing countries. This study was aimed to investigate the effects of appropriate interventions on pregnant women with indicators of MetS to further improve the outcome of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It could also act as a soft power to achieve the geopolitical influence ( 3 , 42 ) deescalate political tensions between and among nations. The practice of health diplomacy also enhances the cohesion of national, regional, and continental efforts to resolve health crises ( 42 ), attain a political reputation in the international arena, and be recognized as a global health benevolant ( 3 ) in reinforcing international peace and stability ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…It could also act as a soft power to achieve the geopolitical influence ( 3 , 42 ) deescalate political tensions between and among nations. The practice of health diplomacy also enhances the cohesion of national, regional, and continental efforts to resolve health crises ( 42 ), attain a political reputation in the international arena, and be recognized as a global health benevolant ( 3 ) in reinforcing international peace and stability ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…We combined the diagnostic criteria of dyslipidemia in general Chinese population and clinical data during pregnancy, pregnant women whose TC > 6.20 mmol/L and TG > 2.30 mmol/L or to either of them were diagnosed with hyperlipidemia. Expect for pregnancy complications [ 15 ], maternal dyslipidemia has also been proved to be closely linked with adverse pregnancy outcomes [ 14 ]. We found that women with hyperlipidemia compared with these in normal lipid group had higher incidence of GDM and cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies described a positive association between gestational dyslipidaemia and the adverse birthweight outcomes [ 13 ]. Additionally, pregnancy-induced hyperlipidemia has also been proved to be closely linked with cesarean delivery and postpartum hemorrhage [ 14 ]. Though moderately increased lipidemia preforms a fundamental role during pregnancy, there are still controversies on the relationship between maternal lipid disturbances and perinatal outcomes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome (MetS) is a global public health issue characterized by cardiovascular risk factors [1][2][3]. MetS are diagnosed if one has 3 or more of the following conditions, obesity, diabetes, hypertension, low HDL or high LDL (also referred here to as conditions related to MetS i.e.…”
Section: Introductionmentioning
confidence: 99%